Islamic Guidance And Counseling Concept For Family Life Readiness Among High School Teenagers - Nurul Choiriyah; Abdul Hayyie Al-Kattani (Prophetic guidance and counseling journal, 2020)
This article explains the concept of Islamic guidance and counselling to help high school students build readiness for marriage and having family life. Marriage and family life readiness is one of aspects in Competency Standards of Independence (SKK) that must be achieved by students at high school level.This concept is similar to the phases and tasks of adolescent development which begin to enter the early adult development phase. The researchers did not find any particularly studies that discuss the concept of Islamic guidance and counseling to help marriage readiness and family life for high school students. Despite the fact that the theme is important to be discussed for further elucidation,the problems eventuates among adolescents, such as premarital sex. The research is conducted by library research method. To support information requirements, researchers also conduct document observations and in-depth interviews with  marriage counselor in Religious Affairs Office (KUA), high school principals, as well as high school guidance counselor and school counselor. The concept of guidance and counselling answers the need and solutions to the problems of adults at the high school level. This also helps to understand family life responsibilities and functions, the concept of reproductive health, what appropriate sexual behaviour is, family norms and relationships between family members.